Isolation, identification, and susceptibility testing of Staphylococcus caprae from dairy goats with mastitis to antibiotics and Chinese herbal medicines - Luo, Jie; Wang, Yiping; Zheng, Wenya; Xu, Chaolong; Chen, Jianhua; Liu, Ben; Wang, Xiaoyue; Fang, Manxin (Frontiers in Veterinary Science, 2025)
IntroductionMastitis outbreaks in dairy goats at a farm in western Jiangxi Province, have recently imposed significant economic losses on farmers. This study aimed to identify the causative pathogen and implement targeted control measures for early disease eradication.MethodsPathological autopsy was performed on diseased goats submitted for examination. Pathological mammary gland tissues and milk cistern fluid were collected aseptically for bacterial isolation and purification. The isolated pathogen was characterized through colony morphology observation, Gram staining, biochemical tests, and 16S rDNA gene sequencing. Pathogenicity was assessed using an animal challenge test in mice. In vitro antibacterial susceptibility testing was conducted using 30 Antibiotics (e.g., cefradine, cephalexin, cefuroxime), 18 Chinese herbal medicines (CHMs; e.g., Rhus chinensis (Galla Chinensis), Coptis chinensis (Chinese Goldthread), Punica granatum (Granati Pericarpium)), and 15 phytogenic extracts (e.g., Berberine, Gallic acid, Tannic acid).ResultsA Gram-positive bacterium was isolated from the diseased tissues. Biochemical profiling and 16S rDNA sequencing identified the isolate as Staphylococcus caprae. The animal challenge test confirmed the isolate’s strong pathogenicity in mice. Susceptibility testing indicated that the isolate was susceptible to Antibiotics such as cefradine, cephalexin, cefuroxime, and ciprofloxacin, while showing the poorest susceptibility to penicillin among the tested antibiotics. Among the CHMs and phytogenic extracts, Rhus chinensis (Galla Chinensis), Coptis chinensis (Chinese Goldthread), Punica granatum (Granati Pericarpium), Berberine, Gallic acid and Tannic acid demonstrated superior antibacterial efficacy.DiscussionThis study provides multiple therapeutic and preventive options (CHMs, Antibiotics, phytogenic extracts) for mastitis control on this farm. It also offers valuable insights into the identification and treatment of mastitis in dairy goats, contributing to safeguarding goat health and ensuring dairy product safety.